Seasonal blood pressure variation assessed by different measurement methods: systematic review and meta-analysis. Issue 5 (May 2020) - Kollias, Anastasios; Kyriakoulis, Konstantinos G.; Stambolliu, Emelina; Ntineri, Angeliki; Anagnostopoulos, Ioannis; Stergiou, George S.
Abstract : Objective: The current study reviewed the published evidence on the seasonal changes in blood pressure (BP) assessed using different measurement methods. Methods: A systematic PubMed/EMBASE search was performed for studies assessing seasonal BP changes. Prospective and cross-sectional studies were included fulfilling the following criteria: (i) report of ambulatory and/or home BP data; (ii) cross-sectional studies reporting only office BP measurements and including 1000 or more participants. Results: Forty-seven studies fulfilled the selection criteria and were included (856 539 participants, weighted age 49.7 ± 4.8 years, 38.8% treated hypertensive patients). The pooled summer minus winter SBP/DBP difference (95% confidence intervals) was office BP (29 studies) −5.6 (−7.1, −4.0)/−3.3 (−4.0, −2.7) mmHg; daytime ambulatory BP (15 studies) −3.4 (−4.4, −2.4)/−2.1 (−2.8, −1.4) mmHg; night-time ambulatory BP (13 studies) 1.3 (0.2, 2.3)/0.5 (−0.2, 1.2) mmHg; home BP (9 studies) −6.1 (−7.0, −5.1)/−3.1 (−3.5, −2.6) mmHg. Meta-analysis of 28 prospective studies ( N  = 5278) which examined the same individuals during different seasons showed pooled seasonal SBP/DBP difference: office BP −5.8/−4.0 mmHg; daytime ambulatory BP −3.9/−2.7 mmHg; night-time ambulatory BP 0.5/−0.5 mmHg; home BP −6.4 /−3.3 mmHg. In meta-regression analysis seasonal systolic daytime ambulatory BP difference was related to the percentage of treated hypertensive patients across studies ( P  = 0.02) and borderline to age ( P  = 0.07). Conclusion: Seasonal BP changes are evident using all daytime BP measurement methods, but not with night-time ambulatory BP. The average BP decline in hot season is at about 5/3 (SBP/DBP) mmHg and appears to be larger in treated hypertensive patients and in older individuals. Abstract : Supplemental Digital Content is available in the text